Reflection in action : a guidebook for student affairs professionals and teaching faculty - Kline, Kimberly A., 1967- (Actionable research for social justice in education and society series., 2014)
"This guidebook aims to stimulate student affairs professionals and higher education faculty alike to adopt new approaches when discussing sensitive or controversial topics with their students. It provides teachers and professionals with a critical social understanding of social justice, social agency, reflection, and actionable knowledge to develop new and effective skills, practice them in safe spaces, and apply them in the field. It offers tools that are equally applicable in a classroom or cocurricular setting."--Page 4 of cover